HUBUNGAN KECEMASAN TERHADAP KEJADIAN DISPEPSIA - Septiani, Listi; Alba, Afif D; Gustina, Nurma Zela (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Dyspepsia is a symptom of the gastroduodenal digestive tract. These symptoms include a painful or burning sensation in the upper abdominal area, a feeling of fullness after eating, or feeling full quickly. The prevalence of dyspepsia in Batam City in 2024 will reach 7.806 people.Dyspepsia is caused by several influencing factors, including psychological factors, namely anxiety. Anxiety that lasts a long time and becomes chronic causes persistent activation effects and hyperactivation of the HPA axis, resulting in excessive cortisol production which can cause direct disturbances in the central nervous system, which innervates the stomach by stimulating the secretion of acetylcholine, gastrin and histamine which ultimately gives rise to complaints of dyspepsia.The aim of this research is to determine the relationship between anxiety and the incidence of dyspepsia in Baloi Permai Subdistrict, Baloi Permai Health Center Working Area, Batam City in 2024. This research includes quantitative research with an analytical design with a cross sectional approach on 57 people affected by dyspepsia. The implementation period is 2 weeks starting from 14 October to 28 October 2024. Sample collection uses the Cluster Random Sampling Technique. The measuring instruments in this study used the Rome IV Criteria questionnaire and the Depression Anxiety Stress Scales (Dass 42). The research results showed that 26 people (45.6%) experienced moderate anxiety and 35 people (61.4%) experienced dyspepsia. The results of the Kolmogorov-Smirnov test showed that there was a relationship between anxiety and the incidence of dyspepsia (p value = 0.001 < 0.05). It is hoped that the results of this research will allow sufferers and the public to make efforts to deal with the problems of dyspepsia and anxiety that occur, as well as becoming reference material for institutions and future researchers that excessive anxiety can cause dyspepsia. Keywords: Dyspepsia, Anxiety